2020
DOI: 10.1371/journal.pone.0240882
|View full text |Cite
|
Sign up to set email alerts
|

Optimal time interval between hysteroscopic polypectomy and frozen-thawed blastocyst transfer: A retrospective study

Abstract: The optimal timing of frozen-thawed blastocyst transfer following hysteroscopic polypectomy is an important and unanswered clinical question. In this study, we conducted a retrospective survey of cases from an infertility center at an academic hospital. We reviewed the charts of all patients who received in-vitro fertilization and frozen-thawed blastocyst transfers (FBT) at the center from January 2009 to November 2019. One hundred and two patients with prior diagnosis of endometrial polyp that were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…21 A randomized control study by Tu-Y-A et al showed a clinical pregnancy rate of 64.8% in frozen embryo transfer following polypectomy. 22 Varates et al and Shokeir et al studies also have shown a positive effect on embryo implantation after endometrial polypectomy. 9,10 Eryilmaz et al study showed IVF outcomes were unrelated to the time interval between the hysteroscopic polypectomy.…”
Section: Discussionmentioning
confidence: 89%
“…21 A randomized control study by Tu-Y-A et al showed a clinical pregnancy rate of 64.8% in frozen embryo transfer following polypectomy. 22 Varates et al and Shokeir et al studies also have shown a positive effect on embryo implantation after endometrial polypectomy. 9,10 Eryilmaz et al study showed IVF outcomes were unrelated to the time interval between the hysteroscopic polypectomy.…”
Section: Discussionmentioning
confidence: 89%
“…Another retrospective study showed that time interval between hysteroscopic polypectomy (n = 205) and embryo transfer, which included a subanalysis of euploid single FET from autologous cycles, did not impact IR, OPR, or early pregnancy loss rates [11]. A more recent retrospective study comparing first FET cycles of women with hysteroscopic polypectomy bluntly via resectoscope cutting loop without diathermy (n = 101) versus women without prior diagnosis of endometrial polyps (n = 102) showed no difference in CPR or LBR between groups if FET was performed within 120 days of polypectomy [20].…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have investigated TI after hysteroscopic polypectomy, [10,16,17] intrauterine adhesions, [18] scratching for endometrial stimulation, [19] or hysteroscopic exploration without tissue biopsy. [9] Tu et al [10] retrospectively studied 102 IVF patients with endometrial polyps who underwent hysteroscopic polypectomy and found that a TI of > 4 months was associated with a decreased rate of successful pregnancy outcomes, thus recommending that these patients wait no longer than 4 months before their next ET cycle. Pereira et al [17] found that patients who underwent ET < 1, 1 to 3, and > 3 months after hysteroscopic polypectomy exhibited no differences in IR, suggesting that they could undergo ET within 1 month after hysteroscopic polypectomy However, Eryilmaz et al [16] concluded that pregnancy outcomes were unrelated to TI, as no significant difference was found in pregnancy outcome rates between patients who underwent ET < 6 months and > 6 months after hysteroscopic polypectomy in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated the time interval (TI) after hysteroscopic polypectomy in patients with endometrial polyps, whereas others have studied TI after hysteroscopic exploration without endometrial biopsy. [9][10][11] However, there are very few reports of TI after hysteroscopic biopsy in patients diagnosed with CE.…”
Section: Introductionmentioning
confidence: 99%